Spider-Gwen : smash / Melissa Flores, writer ; Enid Balam & Alba Glez, pencillers ; Elisabetta D'Amico, inker ; Fer Sifuentes-Sujo, colorist ; VC's Clayton Cowles & Ariana Maher, letterers. - Flores, Melissa (Marvel Worldwide, Inc., 2024)
"The multiversal web-slinger returns! It’s time to face the music when the Mary Janes head off on a four-city tour as the opening act to one of Earth-65’s biggest rock stars! Gwen has promised the band that this big break will be all about the music. No web-slinging, just drums. But when a mysterious assassin targets the headliner, Gwen begins to wonder how she got this gig in the first place. And as the tour continues, she’ll share the stage with stunning new versions of some of your favorite characters – pulling double duty as drummer and secret bodyguard for Dazzler!" --